Locating Nepalese Mobility: A Historical Reappraisal with Reference to North East India, Burma and Tibet - K.C., Gaurab; Kharel, Pranab (Kathmandu School of Law Review, 2018)
Most literature published on migration in Nepal makes the point of reference from 19th century by stressing the Lahure culture—confining the trend’s history centering itself on the 200 years of Nepali men serving in British imperial army. However, the larger story of those non-military and non-janajati (ethnic) Nepali pilgrimages, pastoralists, cultivators and tradesmen who domiciled themselves in Burma, North East India and Tibet has not been well documented in the mobility studies and is least entertained in the popular imagination. Therefore, this paper attempts to catalog this often neglected outmigration trajectory of Nepalis. Migrants venturing into Burma and North East India consist of an inclusive nature as the imperial army saw the overwhelming presence of hill janajatis in their ranks whereas Brahmins (popularly known as Bahuns) and Chettris were largely self-employed in dairy farming and animal husbandry. In tracing out the mobility of Nepalis to North East, Burma and Tibet it can be argued that the migrating population took various forms such as wanderers (later they became settlers), mercantilist, laborers, mercenary soldiers, and those settlers finally forced to become returnees. In this connection, documenting lived experiences of the living members or their ancestors is of paramount importance before the memory crosses the Rubicon.DOI: https://doi.org/10.46985/jms.v6i2.208